1995
DOI: 10.1161/01.str.26.2.318
|View full text |Cite
|
Sign up to set email alerts
|

Transient Increase of Cytokine-Induced Neutrophil Chemoattractant, a Member of the Interleukin-8 Family, in Ischemic Brain Areas After Focal Ischemia in Rats

Abstract: A marked increase in CINC concentration was detected in brain and serum during early reperfusion. This suggests that the time course of CINC production precedes brain edema formation and neutrophilic infiltration. It thus appears that CINC may play an important role in neutrophilic infiltration in ischemic lesion and in brain edema formation after ischemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(59 citation statements)
references
References 30 publications
3
55
0
1
Order By: Relevance
“…Another group observed increased CINC expression in the brain and serum 3 ± 12 h after reperfusion. One hour of ischemia without reperfusion did not produce increase in CINC expression in the brain (Yamasaki et al, 1995).…”
Section: Chemokines In Nonimmunologic Cns Injurymentioning
confidence: 75%
“…Another group observed increased CINC expression in the brain and serum 3 ± 12 h after reperfusion. One hour of ischemia without reperfusion did not produce increase in CINC expression in the brain (Yamasaki et al, 1995).…”
Section: Chemokines In Nonimmunologic Cns Injurymentioning
confidence: 75%
“…Interleukin-1b (IL-1b) is a pro-inflammatory cytokine which is released by a variety of cell types, including peripheral immune cells as well as cells of the CNS-like astrocytes, microglia and some neurones (Dinarello 1988;Hopkins and Rothwell 1995). It serves a broad array of functions both in the periphery and in the CNS, and is involved in the immune-to-brain communication initiating the so-called Ôsickness responseÕ, such as the induction of fever in response to an invasion by a pathogen (for review see Rothwell 1997).Within the CNS, IL-1b is increased in response to brain injury and subsequently regulates the brain's inflammatory response by stimulating the production of other cytokines, such as IL-6 and IL-8, as well as inducible nitric oxide synthase (iNOS), chemotactic factors and adhesion molecules, for attracting peripheral mononuclear cells to cross the blood-brain barrier (Benveniste et al 1990;Yamasaki et al 1995;. In cases such as cerebral ischaemia and excitotoxic brain injury, IL-1b levels dramatically increase in the brain within few hours (Minami et al 1991;Woodroofe et al 1991;Taupin et al 1993), and several studies have shown that inhibition or gene disruption of the Received March 12, 2002; revised manuscript received July 18, 2002; accepted August 19, 2002.…”
mentioning
confidence: 99%
“…Within the CNS, IL-1b is increased in response to brain injury and subsequently regulates the brain's inflammatory response by stimulating the production of other cytokines, such as IL-6 and IL-8, as well as inducible nitric oxide synthase (iNOS), chemotactic factors and adhesion molecules, for attracting peripheral mononuclear cells to cross the blood-brain barrier (Benveniste et al 1990;Yamasaki et al 1995;. In cases such as cerebral ischaemia and excitotoxic brain injury, IL-1b levels dramatically increase in the brain within few hours (Minami et al 1991;Woodroofe et al 1991;Taupin et al 1993), and several studies have shown that inhibition or gene disruption of the IL-1b-converting enzyme (ICE or caspase 1) or overexpression of IL-1 receptor antagonist (IL-1ra) results in neuroprotection (Relton and Rothwell 1992;Loddick et al 1996;Schielke et al 1998).…”
mentioning
confidence: 99%
“…TNF-α recruits and activates leukocytes, leading to increased leukocyte-endothelial adhesion (Fabry et al, 1992;Liu et al, 1994), which progressively induces expression of other cytokines, including IL-1, IL-6, IL-8 and so on, thus forming a positive feedback loop further exacerbating brain injury. Levels of TNF-α, IL-1 and IL-8 are positively correlated proportionably to neurons damage, brain edema and infarction extension, and can serve as good indicators of cerebral ischemia-reperfusion injury (Yamasaki et al, 1995;Barone et al, 1997;Yang et al, 1997). Elevated serum IL-8 and TNF-α levels comprise the worse outcome in patients following out-of-hospital cardiac arrest (Ito et al, 2001).…”
Section: Discussionmentioning
confidence: 99%